ESTUDIO ECONÓMICO PARA LA CREACIÓN DE UNA EMPRESA DE SERVICIOS DE TRANSPORTE TERRESTRE EN LA PARROQUIA CAPIRO - CANTÓN PIÑAS - Aguilar Castro, Angel Gabriel (2019)
The "ECONOMIC STUDY FOR THE CREATION OF AN EARTH TRANSPORTATION SERVICES COMPANY IN THE CAPIRO - CANTON PIÑAS PARISH", was carried out to know the feasibility and feasibility to create a transport cooperative, the respective market, technical, economic study was elaborated and its financial evaluation; The main objective is the determination of costs, the obtaining of the total amount of the investment and the financing sources that are required for its execution, emphasizing the organisms or persons from whom the money will be obtained to proceed to invest and generate the service. For the determination of costs quotes were made between different sales houses, these costs were supported by invoices and proformas delivered by the houses of acquisition in order to achieve a logical and sustained cost reaching to obtain the required budgets and the statement of results . The costs for the provision of the service were obtained, which are of $ 4,350.05; likewise, administration costs that reach $ 930.50; the financial costs with an annual value of $ 21,853.62 and the costs of sales that are $ 1,349.97. Next, the initial fixed and deferred investment was calculated, detailing all the tangible assets (Transport Units, Computing Equipment, Printers, Office Furniture and Furniture and Appliances) that amount to $ 337,956.63; as intangible (Constitution and Organization Expenses, Preliminary Studies, Installation Expenses, etc.) that grant us a value of 5 1,100.00; In the same way, the respective quotation was made between different buying houses, comparing and selecting the best investment to be made in order to know what the investment in assets that the transport company is going to have at the time of its operation. In relation to financing, the credit to be acquired will be made to the BanEcuador financial institution; because it is a very favorable option since the term for payment of $ 200,000.00 plus their respective interests is 5 years in relation to other institutions; subsequently, the respective debt amortization table was prepared to know the interest and fees that must be paid periodically. With the results obtained, it was concluded that the projection of annual income of $ 113,400.00 in relation to the determination of annual costs of $ 75,732.13 is totally favorable, so the opening of the transport company would generate a considerable profit per period. With the investment to be made it is intended to offer a service according to the user and of first quality, it should be noted that the execution of this work comes hand in hand with the growth and economic and social development of the town.